Photoprotective effects of Sargassum thunbergii on ultraviolet B-induced mouse L929 fibroblasts and zebrafish - Bei Chen; Honghong Chen; Haidong Qu; Kun Qiao; Min Xu; Jingna Wu; Yongchang Su; Yan Shi; Zhiyu Liu; Qin Wang (BMC, 2022)
Abstract Background Chronic exposure to ultraviolet B (UVB) causes a series of adverse skin reactions, such as erythema, sunburn, photoaging, and cancer, by altering signaling pathways related to inflammation, oxidative stress, and DNA damage. Marine algae have abundant amounts and varieties of bioactive compounds that possess antioxidant and anti-inflammatory properties. Thus, the objective of this study was to investigate the photoprotective effects of an ethanol extract of Sargassum thunbergii. Methods Sargassum thunbergii phenolic-rich extract (STPE) was prepared, and its activity against UVB damage was evaluated using L929 fibroblast cells and zebrafish. STPE was extracted and purified by 40% ethanol and macroporous resin XDA-7. Reactive oxygen species (ROS) and antioxidant markers, such as superoxide dismutase (SOD), catalase (CAT) activities, and malondialdehyde (MDA) content were analyzed. The effect of STPE on UVB-induced inflammation was determined by inflammatory cytokine gene and protein expression. The expression of signaling molecules in the Nuclear Factor KappaB (NF-κB) pathway was determined by western blotting. DNA condensation was analyzed and visualized by Hoechst 33342 staining. In vivo evaluation was performed by tail fin area and ROS measurement using the zebrafish model. Results The total polyphenol content of STPE was 72%. STPE reduced ROS content in L929 cells, improved SOD and CAT activities, and significantly reduced MDA content, thereby effectively alleviating UVB radiation-induced oxidative damage. STPE inhibited the mRNA and protein expression of TNF-α, IL-6, and IL-1α. STPE reversed DNA condensation at concentrations of 20 and 40 μg/mL compared with the UVB control. Moreover, STPE inhibited NF-κB signaling pathway activation and alleviated DNA agglutination in L929 cells after UVB irradiation. Additionally, 1.67 μg/mL STPE significantly increased the tail fin area in zebrafish, and 0.8-1.6 μg/mL STPE effectively eliminated excessive ROS after UVB radiation. Conclusions STPE inhibited UVB-induced oxidative stress, inflammatory cytokine expression, and DNA condensation via the downregulation of the NF-κB signaling pathway, suggesting that it prevents UVB-induced photodamage, and has potential for clinical development for skin disease treatment.